Copyright Protection In Digital Rights Management Systems: Legal And Technical Challenges In Implementing Effective Solutions - Aenul Yaqin; Dewi Sulistianingsih (Universitas Negeri Semarang, 2024)
This research aims to examine copyright protection against unlawful acts, particularly in the context of piracy and claims over songs in the era of disruption. Through a normative juridical approach and data collection techniques via library research, this study explores the theoretical foundations of justice in law, the definition of unlawful acts, and the urgency of copyright protection for musical works. In-depth analysis is conducted on copyright discourse concerning music piracy, as well as the concept of legal protection that offers solutions and ideals for piracy or claims over songs. The research findings indicate that song piracy is not merely a common legal violation but also threatens the economic sustainability and creativity of music creators. Therefore, copyright protection must be accompanied by proactive preventive measures and effective law enforcement. In conclusion, copyright protection is a prerequisite for achieving justice in the music industry in the current digital era, requiring cross-sector collaboration and policy innovation to address the challenges faced.